Circular migration - Klaus F. Zimmermann (IZA World of Labor, 2014)
In the popular immigration narrative, migrants leave one country and establish themselves permanently in another, creating a "brain drain" in the sending country. In reality, migration is typically temporary: Workers migrate, find employment, and then return home or move on, often multiple times. Sending countries benefit from remittances while workers are abroad and from enhanced human capital when they return, while receiving countries fill labor shortages. Policies impeding circular migration can be costly to both sending and receiving countries.
Keywords: J61; F22; F24; 330; labor mobility; temporary movements; guest workers; repeat migration; cyclical migration; circular migration